E-learning readiness among medical educators in Universiti Sains Islam Malaysia - Khalid, Salleha; Tengku Mohd, Tengku Amatullah Madeehah; Abang Abdullah, Khadijah Hassanah; Sanip, Suhaila; Mohd Aris, Muhammad Shamsir; Sharif, Khaironi Yatim; Mohd Mokthar, (Science Publications, 2014)
Recent advances in information technology has made e-learning feasible in many fields of education. Medical education is not any different. This survey is conducted among all the medical educators in Universiti Sains Islam Malaysia (USIM) assessing their readiness and attitudes towards e-learning. A cross-sectional questionnaires assessing the IT skills, Internet usage, attitude, perceived benefits and usage of e-learning among USIM medical lecturers were used. Data gained were then analyzed. The response rate was 92%. Female (56) made majority of the respondents. 44 of the educators aged 25-34 with 56% had teaching experience of <5 years. Majority of the respondents rate their skills as intermediate in using the software. 56% uses the Internet for more than 3 h per day. Majority agreed that e-learning benefits the students in many ways. Majority also willing to learn and integrate e-learning in their teaching modalities. Despite this, many have not used e-learning in delivering lectures and accepting assignments at time of the survey. Nevertheless, while majority of medical educators are willing to incorporate e-learning in their teaching, many still have not used it. Improvement of infrastructure, training and support to all medical educators are required for successful implementation of e-learning.